PENINGKATAN KEMAMPUAN MEMBEDAKAN FAKTA DAN OPINI MELALUI MEDIA ZONA DETEKTIF BERBASIS PROYEK POSTER SISWA KELAS DASAR - Willis Niki Suryadita; Dede Nuraida; Sri Rahayu Puji Lestari (STKIP Subang, 2026)
This Classroom Action Research (CAR) aims to improve the ability to distinguish between fact and opinion sentences among fifth-grade students through the implementation of the